Effect of iron deficiency anemia during pregnancy on T3, T 4 and TSH levels in newborns - Suratmin Suratmin; Siska Mayasari Lubis; Melda Deliana; Hakimi Hakimi (Indonesian Pediatric Society, 2011)
Background Iron deficiency anemia (IDA) in infants is associatedÂ v.ith maternal iron deficiency anemia during pregnancy. InfantsÂ from anemic mothers often have lower hemoglobin levels thanÂ those from nonô€anemic mothers. S everal studies have suggestedÂ that IDA in infants can impair thyroid peroxidase (TPO) enzymeÂ which is required to produce thyroid hormones.Â Objective To detennine the effects of IDA during pregnancy onÂ T3, T4, and TSH levels in newborns.Methods We conducted a crossô€sectional study from September toÂ December 2010 in two hospitals. Mothers' blood specimens wereÂ examined for IDA. Newborns' hematocrit, hemoglobin, ferritin,Â T3, T4, and TSH levels were measured in umbilical vein bloodspecimens taken at 24 hours of life.Results Mean T3, T4, and TSH levels of 40 newborns whoseÂ mothers suffered from IDA were 2.2 nmollL (SD 1.19), 8.4 ug/dL (SD 6.12), and 15.3 mIU/mL (SD 3.99), Â respectively. ThereÂ was no significant relationship between maternal IDA duringpregnancy and infant T3 and TSH levels (P=0.96, P=0.29,Â respectively ). However, maternal IDA significantly correlatedÂ 'With infant T4 levels.Conclusion There was no significant relationship betweenÂ maternal IDA during pregnancy and levels of T3 and TSH inÂ newborns. However, maternal IDA significantly correlated withÂ lower infant T4 levels.